Modelling centralization of pancreatic surgery in a nationwide analysis. Issue 11 (27th June 2020) - Balzano, G.; Guarneri, G.; Pecorelli, N.; Paiella, S.; Rancoita, P. M. V.; Bassi, C.; Falconi, M.
Abstract : Background: The benefits of centralization of pancreatic surgery have been documented, but policy differs between countries. This study aimed to model various centralization criteria for their effect on a nationwide cohort. Methods: Data on all pancreatic resections performed between 2014 and 2016 were obtained from the Italian Ministry of Health. Mortality was assessed for different hospital volume categories and for each individual facility. Observed mortality and risk‐standardized mortality rate (RSMR) were calculated. Various models of centralization were tested by applying volume criteria alone or in combination with mortality thresholds. Results: A total of 395 hospitals performed 12 662 resections; 305 hospitals were in the very low‐volume category (mean 2·6 resections per year). The nationwide mortality rate was 6·2 per cent, increasing progressively from 3·1 per cent in very high‐volume to 10·6 per cent in very low‐volume hospitals. For the purposes of centralization, applying a minimum volume threshold of at least ten resections per year would lead to selection of 92 facilities, with an overall mortality rate of 5·3 per cent. However, the mortality rate would exceed 5 per cent in 48 hospitals and be greater than 10 per cent in 17. If the minimum volume were 25 resections per year, the overall mortality rate would be 4·7 per cent in 38 facilities, but still over 5 per cent in 17 centres and more than 10 per cent in five. The combination of a volume requirement (at least 10 resections per year) with a mortality threshold (maximum RSMR 5 or 10 per cent) would allow exclusion of facilities with unacceptable results, yielding a lower overall mortality rate (2·7 per cent in 45 hospitals or 4·2 per cent in 76 respectively). Conclusion: The best performance model for centralization involved a threshold for volume combined with a mortality threshold. Abstract : The use of a minimal volume requirement as the sole criterion for a centralization policy could prove inadequate as some hospitals with high mortality rate could be selected. A mortality threshold should be combined with a minimal volume requirement to improve hospital selection. Models involve volume and mortality Abstract : Antecedentes: Los beneficios de la centralización de la cirugía pancreática están bien documentados, pero la política de actuación difiere entre los países. Este estudio tuvo como objetivo desarrollar modelos de centralización basados en varios criterios y analizar su aplicación en una cohorte nacional. Métodos: Los datos de todas las resecciones pancreáticas realizadas entre 2014 y 2016 se obtuvieron del Ministerio de Salud italiano. La mortalidad se evaluó para diferentes categorías del volumen hospitalario y para cada centro individualmente. Se calculó la mortalidad observada y la tasa estandarizada de riesgo de mortalidad ( risk standardized mortality rate, RSMR). Se analizaron varios modelos de centralización aplicando criterios de volumen solos o en combinación con umbrales de mortalidad. Resultados: Un total de 395 hospitales realizaron 12.662 resecciones; 305 de ellos pertenecían a la categoría de muy bajo volumen (media de 2, 6 resecciones/año). La mortalidad nacional fue del 6, 2%, aumentando progresivamente del 3, 1% en los hospitales de muy alto volumen al 10, 6% en los hospitales de muy bajo volumen. Para fines de centralización, al aplicar un umbral de volumen mínimo ≥ 10 resecciones/año, se seleccionarían 92 centros, con una mortalidad global del 5, 3%. Sin embargo, la mortalidad sería > 5% en 48 hospitales y > 10% en 17 hospitales. Si el volumen mínimo fuera de 25 resecciones/año, la mortalidad global sería del 4, 7% en 38 hospitales, pero aún > 5% en 17 centros y > 10% en seis centros. La combinación de un volumen necesario (≥ 10 resecciones/año) con un umbral de mortalidad (RSMR ≤ 5% o ≤ 10%) permitiría excluir hospitales con resultados inaceptables, determinando una mortalidad global más baja (2, 7% en 45 hospitales o 4, 2% en 76 hospitales, respectivamente). Conclusión: El mejor modelo para la centralización de resecciones pancreáticas incluyó un umbral para el volumen hospitalario combinado con un umbral de mortalidad.